Shift in Immune Parameters After Repeated Exposure to Nanoplastics in the Marine Bivalve Mytilus - Auguste, Manon; Balbi, Teresa; Ciacci, Caterina; Canonico, Barbara; Papa, Stefano; Borello, Alessio; Vezzulli, Luigi; Canesi, Laura (Frontiers in Immunology, 2020)
Invertebrates can adapt and survive in virtually any ecosystem by only relying on innate immunity. This implies the presence of complex and sophisticate mechanisms of immune specificity, and the capacity to mount a faster/more effective response upon re-exposure to a stimulus (‘immune training/priming’). Bivalves are widespread in coastal environments subjected to a wide range of environmental fluctuations: however, the rapidly occurring changes due to several anthropogenic factors can represent a significant threat to bivalve immunity. The mussel Mytilus spp. has extremely powerful immune defenses to cope with different potential pathogens and contaminant stressors. In particular, mussel immune system represents a significant target for different types of nanoparticles-NPs, including amino modified polystyrene-PS-NH2 as a model of nanoplastics. In this work, the effects of repeated exposure to PS-NH2 on immune responses of M. galloprovincialis were investigated after a I exposure (10 µg/L; 24h), followed by a resting period (72h depuration) and a II exposure (10 µg/L; 24h). Functional parameters were measured in hemocytes (mitochondrial and lysosomal markers, phagocytosis and oxidative burst), serum (lysozyme activity), and whole hemolymph (THC, hemocyte subpopulations, bactericidal activity towards Vibrio aestuarianus). In hemocytes, transcription of proliferation and apoptotic markers, as well as of six immune related genes, was evaluated by qPCR. I exposure to PS-NH2 significantly affected hemocyte mitochondrial and lysosomal parameters, serum lysozyme activity and transcription of proliferation/apoptosis markers; up and down regulation of 1 and 2 immune related genes, respectively, was observed. All other parameters were unaffected. The results indicate the occurrence of stress conditions, that did not however result in changes in the overall bactericidal activity. After II exposure, a shift in granular hemocyte subpopulations, together with re-establishment of basal functional parameters and of proliferation/apoptotic markers were observed. Moreover, hemolymph bactericidal activity, as well as transcription of 5 out of 6 immune related genes, all codifying for secreted proteins, were increased. The results indicate both tolerance and potentiation as compensatory mechanisms to maintain immune homeostasis after a second encounter with PS-NH2, representing a form of immune memory.